ECHOCHARDIOGRAPHIC FEATURES AND CAROTID SCORE IN PATIENTS OLDER THAN 65 YEARS WITH TYPE 2 DIABETES MELLITUS AND HEART FAILURE - Veterovska Miljkovic, Lidija Simeon; Jordanovski, Lazo; Ivanovska, Marika; Brezovska, Elena; Gaspar, Glorija; Pavleska, Lidija (Journal of Morphological Sciences; Vol 7 No 2 (2024): JMS, 2024)
Evaluation of arterial stiffness and carotid atherosclerotic burden, as well as echocardiographic structural changes, can provide important prognostic information regarding the risk of future cardiovascular events. The aim of this study was to assess these vascular properties in patients with diabetes mellitus type 2 ( DM type 2) and heart failure with preserved ejection fraction (HFpEF), older than 65 years.    In our research we analyzed 124 participants older than 65 years, 85 of them were with determined diabetes mellitus status, heart failure (HF) is accompanied by an preserved ejection fraction, diagnosed clinically and by echocardiography. In the control group were subjects older than 65 years, without DM type 2 and HFpEF. Carotid ultrasonography was performed to evaluate intima - media thickness (IMT) and carotid plaque burden. Echocardiographic measurements were performed according to criteria ESC/ASC( 2015). The carotid score - IMT and the presence of plaques in the carotid vessels were significantly correlated with the severity and duration of  the diseases. Structural changes of the heart such as left atrial dilatation, left ventricular hypertrophy, the degree of diastolic dysfunction verified by echocardiography were correlated with the severity of heart failure and DM type 2    Echocardiographic abnormalities are very common in elderly patients with DM type 2 and HFpEF  and differed from the control group of patients. They, along with carotid score strongly correlate with disease severity and the possibility of future cardiovascular events. Key words : elderly, diabetes mellitus type 2, heart failure, echocardiography, carotid score